Decentring the avant-garde - Bäckström, Per; Hjartarson, Benedikt (Avant garde critical studies ;, 2014)
"Decentring the Avant-Garde presents a collection of articles dealing with the topography of the avant-garde. The focus is on different responses to avant-garde aesthetics in regions traditionally depicted as cultural, geographical and linguistic peripheries. Avant-garde activities in the periphery have to date mostly been described in terms of a passive reception of new artistic trends and currents originating in cultural centres such as Paris or Berlin. Contesting this traditional view, Decentring the Avant-Garde highlights the importance of analysing the avant-garde in the periphery in terms of an active appropriation of avant-garde aesthetics within different cultural, ideological and historical settings. A broad collection of case studies discusses the activities of movements and artists in various regions in Europe and beyond. The result is a new topographical model of the international avant-garde and its cultural practices"--